1999
DOI: 10.1097/00002030-199910010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Baseline HIV drug resistance profile predicts response to ritonavir-saquinavir protease inhibitor therapy in a community setting

Abstract: Baseline resistance to ritonavir or saquinavir or both was associated with a poor antiviral response. Our data suggest that the measurement of drug resistance may assist in optimizing antiretroviral therapy in the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 14 publications
3
75
0
Order By: Relevance
“…Third, the signed-sum method used in the multivariate analysis of the genotypic patterns helped to simplify complex data and avoid the potential problem of colinearity between mutation predictors. Finally, recent retrospective studies support our findings, although not all of these studies have shown that the predictive capacity of resistance testing is independent of standard clinical predictors (37,(53)(54)(55)(56).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Third, the signed-sum method used in the multivariate analysis of the genotypic patterns helped to simplify complex data and avoid the potential problem of colinearity between mutation predictors. Finally, recent retrospective studies support our findings, although not all of these studies have shown that the predictive capacity of resistance testing is independent of standard clinical predictors (37,(53)(54)(55)(56).…”
Section: Discussionsupporting
confidence: 83%
“…Mutations at these codons are known to be associated with resistance to one of the nucleoside reverse transcriptase inhibitors (25,45). In the protease gene, mutations at codons 30,46,48,54,82,84, and 90 were evaluated as potential predictors. We chose these "major" mutations a priori because they are associated with in vitro resistance to a protease inhibitor or occur commonly in patients in whom therapy with currently licensed protease inhibitors is failing.…”
Section: Hiv Genotypingmentioning
confidence: 99%
“…due position 93 are associated with virological failure to saquinavir in combination with ritonavir [42,49]. Although the other polymorphisms in the C-SA protease have not been associated with virological failure in clinical studies, they may still contribute to the observed reduced drug susceptibility of the C-SA protease.…”
Section: Effect Of Secondary Resistance Mutations On Flap Movementmentioning
confidence: 97%
“…The M36I mutation is the only polymorphic mutation in the C-SA protease that is associated with drug resistance to most of the FDAapproved PIs in combination with ritonavir [41]. This mutation is associated with virological failure or a reduced virological response to atazanavir, darunavir, fosamprenavir, indinavir, lopinavir, saquinavir and tipranavir in combination with ritonavir [42][43][44][45][46][47][48][49]. Mutations at residue position 89 are associated with virological failure to darunavir and tipranavir in combination with ritonavir [44,50], and mutations at resi- In the subtype B protease (A) (PDB ID: 2PC0 [13]), M36 appears to provide anchorage for E35, and stabilizes the salt bridge between E35 and R57.…”
Section: Effect Of Secondary Resistance Mutations On Flap Movementmentioning
confidence: 99%
“…In addition, the emergence of HIV strains resistant to HAART has posed serious concerns for the viability of future treatments [164]. Most individuals discontinuing suppressive therapy have a rapid rebound in plasma viremia [165][166][167][168][169]. One explanation for this observation is the persistence of the virus in biological reservoirs.…”
Section: Hiv-1 Infectivity In Macrophagesmentioning
confidence: 99%